2022
DOI: 10.1002/ijgo.14404
|View full text |Cite
|
Sign up to set email alerts
|

Support strategies for pregnant women and their offspring in disaster events

Abstract: Working in the shadows, under the spotlight -reflections on lessons learnt in the Republic of Ireland after the first 18 months of more liberal abortion care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Pregnant women and newborns are vulnerable in times of disaster, and recent large-scale disasters in various locations worldwide have had a major impact on these patient groups. [4][5][6][7][8][9] Several studies have reported higher rates of preterm births and low-birth-weight infants during large-scale disasters. [10][11][12] In areas affected by the Great East Japan Earthquake, future need of a new acute perinatal care management system was identified, focused on the special needs of affected pregnant and nursing mothers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women and newborns are vulnerable in times of disaster, and recent large-scale disasters in various locations worldwide have had a major impact on these patient groups. [4][5][6][7][8][9] Several studies have reported higher rates of preterm births and low-birth-weight infants during large-scale disasters. [10][11][12] In areas affected by the Great East Japan Earthquake, future need of a new acute perinatal care management system was identified, focused on the special needs of affected pregnant and nursing mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women and newborns are vulnerable in times of disaster, and recent large‐scale disasters in various locations worldwide have had a major impact on these patient groups 4–9 . Several studies have reported higher rates of preterm births and low‐birth‐weight infants during large‐scale disasters 10–12 .…”
Section: Discussionmentioning
confidence: 99%